A STUDY OF THE POTENCY OF PIPELLE BIOPSY TECHNIQUE TO DETECT ENDOMETRIAL DISEASE IN PERIMENOPAUSAL / POSTMENOPAUSAL WOMEN - Amin, Nabila; Yazdani, Tehreem; Kareem, Farhat (Pakistan Armed Forces Medical Journal, 2020)
Objective: To see the efficacy of the gynecological procedure of outdoor endometrial biopsy using pipelle biopsy.Study Design: Prospective observational study.Place and Duration of Study: Sampling was done at obstetrics and gynecology department Pak-Emirates Military Hospital Rawalpindi, from Jan 2018 to Aug 2018.Methodology: A 100 cases of perimenopausal/postmenopausal women presenting with menorrhagia/menorrhagia after the age of 40 years were selected for the study. Pipelle biopsy was employed in all the cases.Results: The patients presenting with metorrhagia, menorrhagia, polymennorrhagia and postmenopausal bleeding with mean age of 46 ± 3.26 were included in the study. Sixty eight (68%) patients had metorrhagia, 10 (10%) presented with menorrhagia, 10 (10%) patients had polymennorrhagia while 12 (12%) patients had postmenopausal bleeding. Histopathological results showed that 5 (5%) patients were suffering from chronic endometriosis, 20 (20%) had hormonal imbalances, 45 (45%) had proliferative endometrium, 18 (18%) had endo-metrial benign hyperplasia.Conclusion: It is concluded that outdoor endometrial conventional biopsy using pipelle biopsyis cost-effective and convenient method for diagnosing endometrial diseases. The procedure while providing reliable histopathological results in all cases is cheap and causes minimal discomfort to patients.